Pengembangan Multimedia Interaktif Berbasis Articulate Storyline dengan Pendekatan RME Pada Materi Pengukuran Waktu Kelas II SD - Giska Marcellia; Yantoro; Muhammad Sholeh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the limitations of mathematics learning media on the Time Measurement material in class II of SD Negeri 174/IV Jambi City. The learning process is still one-way with the teacher as the center of activity, while the available media is limited, only in the form of pictures from textbooks. This condition causes students to have difficulty understanding the material and their low involvement in the learning process. This research aims to develop interactive multimedia based on Articulate Storyline with a Realistic Mathematics Education (RME) approach to increase active involvement and understanding of student concepts. The method used is research and development (R&D) with the DDD-E model, including the stages of Decide, Design, Reveal (Develop), and Evaluate. The developed product contains materials, videos, and interactive quizzes that are in accordance with Phase A Mathematics Learning Outcomes and student characteristics. The expert validation results show a validity level of 96% (Very Valid) for the language aspect, 94% (Very Valid) for the media, and 78.18% (Valid) for the material, while the practicality test shows 90% (Very Practical) for the teacher, 87% (Very Practical) for the small group, and 93.33% (Very Practical) for the large group. This confirms that this multimedia is feasible and easy to use. This interactive multimedia has the potential to increase student engagement, strengthen understanding of the concept of time measurement, and develop critical and creative thinking skills. This development opens up opportunities for applying similar media to other materials with the integration of additional digital features to enrich the learning experience of students.